Manifestations of beliefs in mystical (“tuah”) plants within the repertoires and practice of Javanese karawitan - Tejo Bagus Sunaryo; Lasiyo Lasiyo; Heri Santoso (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
Javanese culture maintains a profound relationship with mysticism, including beliefs in plants considered to possess tuah(spiritual potency). Javanese karawitan, as a cultural expression, also contains symbolic layers shaped by these mystical worldviews. This study examines how such beliefs manifest in the titles, symbolic atmospheres, and performative behaviors associated with selected gendhings that reference or imply spiritually potent plants. Using a qualitative descriptive method and a phenomenological approach grounded in Javanese cultural mysticism, the research integrates musical-text analysis, cosmological symbol interpretation, and interviews with practitioners to clarify how each method contributes to the findings. Textual analysis identifies plant-related symbolic markers; phenomenological interpretation reveals how performers internalize these symbols; interviews explain the cultural logic linking plant potency with specific performative behaviors. The findings show that beliefs in spiritually potent plants function not merely as a cosmological background but as active determinants of performative intention, aesthetic atmosphere, and interpretive meaning within the examined repertoire. This study offers a new contribution by demonstrating that the concept of tuah operates as a metaphysical structure influencing both musical creation and performance. Unlike previous studies, it identifies a direct relationship between sacred-plant symbolism and its concrete manifestation in Javanese karawitan.